UJI AKTIVITAS ANTIOKSIDAN DAN TOKSISITAS EKSTRAK N- HEKSAN DAN ETIL ASETAT RANTING SIRIH HUTAN (Piper aduncum L.) - Yerwanto Ilang; Syelvia Lousiana Kalauw; Rudi Kartika; Fauzi Rachman (PROSIDING SEMINAR KIMIA, 2014)
The aim of this study was to determine the antio xidant and toxicity act ivities of n-hexane and ethyl acetate of Piper aduncum L. (family : Piperaceae). Antio xidant activities of the ext racts was assessed by means of DPPH free radical scavenging method used ascorbic acid as standard with IC 50 value was 4,841 μg/mL. Piper aduncum L. showed n-hexane extract demonstrated the good antioxidant activity with IC 50 value of 40,034 μg/ mL and the ethyl acetate extract is 59,838 μg/ mL. The Brine shrimp letality bioassay met od as sed to determine t e cytotoxicity activities. The LC 50 values of n-hexane and ethyl acetate extracts were 25,12 and 17,78 μg/ mL, respectively.